Мова п'єси Лесі Українки "Руфін і Прісцілла": текстолого-семантичний аспект - Гаджилова, Г. (Культура слова, 2020)
У статті здійснено текстологічний і мовно-стилістичний аналіз тексту драми Лесі Українки «Руфін і Прісцілла». Джерелом дослідження є не лише друкований текст, а й рукописний текст чорнового автографа драми. З’ясовано мотиви й засоби авторського редагування тексту, простежено роботу авторки над художнім удосконаленням драми, організацією мовних засобів, розглянуто їх еволюцію, процес стилістичного вдосконалення тексту. Доведено, що Леся Українка відшліфовує текст на межі тонких семантичних відтінків. The article provides a textual, linguistic and stylistic analysis of the text of Lesіa Ukrainka’s drama “Rufin and Priscilla” and its variants. The source of the study is not only the printed text, but also the handwritten text of the draft autograph of the mentioned drama and several layers presented in it. The motives and means of self-editing of the text were specified, the work of the author on the artistic improvement of the drama as well as the organization of language means were traced, their evolution and the process of stylistic improvement of the text were studied. It was proved that Lesіa Ukrainka attached great importance to the choice of synonyms, looked for words that would most accurately convey subtle semantic nuances. When editing the text, the author tried to find accurate expressions, words that more accurately, more clearly convey the idea; worked on each line, made the expressions more psychologically accurate, emotionally rich and more expressive. Lesіa Ukrainka “smoothed out” the drama, reflecting on every word, made changes that raise the artistic level of the work, facilitate pronunciation, and express the sound. Words, which do not carry a semantic charge or duplicate what had already been said in the text, Lesіa Ukrainka, altered and got the artistically better versions. The author extensively used the syntactic means of stylistics, skillfully identified the necessary word with the help of stylistic capacity of syntax. It was proved that Lesіa Ukrainka used the forms, categories and shades of the meanings of verbs, which are ones of the most stylistically noticeable parts of the language. The analyzed examples testify to Lesіa Ukrainka’s thorough work on the text, the organization of language means focused on the emotionally evaluative, multifaceted and expressive perspective of dynamic presentation. The playwright tried to find semantically and psychologically balanced expressions, to choose words that would most accurately define the speaker and the nature of the action and improved the stretched stanzas. When choosing the language means, Lesіa Ukrainka preferred emotionally rich, expressively colored words, avoided the statements that distract the attention at climaxes, selected the most semantically and psychologically accurate expressions that would create the desired situation, motivate the thoughts and the behavior of the actors and the nature of action.